2020
DOI: 10.1177/0967391120905705
|View full text |Cite
|
Sign up to set email alerts
|

Parametric optimization of laser drilling of microwave-processed kenaf/HDPE composite

Abstract: The present work focused on the investigation of hole quality characteristics in laser-drilled kenaf/high-density polyethylene (HDPE) composites. Microwave-assisted compression molding was used to fabricate kenaf/HDPE composite with 20 wt% of the kenaf fiber reinforcement. The two input parameters pertaining to the experimentation were laser power and cutting speed. Kerf taper angle, heat-affected zone (HAZ), and surface roughness were investigated to evaluate the surface quality and accuracy of the holes gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…Traverse speed rank came second in terms of effect on the HAZ, and its contribution increased with the thickness of the material. The minimum HAZ was recorded at minimum values of laser power in general, except for the case of 6 mm specimen thickness, where the optimum HAZ was recorded with a medium laser power value, which differs slightly from that recorded at the minimum value of laser power, and this is consistent with the results of the study conducted by Tewari et al [23]. The laser power parameter contributed the least to the influence on the HAZ with no clear proportion with material thickness variation, and this is consistent with what Tamrin et al [22] found.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Traverse speed rank came second in terms of effect on the HAZ, and its contribution increased with the thickness of the material. The minimum HAZ was recorded at minimum values of laser power in general, except for the case of 6 mm specimen thickness, where the optimum HAZ was recorded with a medium laser power value, which differs slightly from that recorded at the minimum value of laser power, and this is consistent with the results of the study conducted by Tewari et al [23]. The laser power parameter contributed the least to the influence on the HAZ with no clear proportion with material thickness variation, and this is consistent with what Tamrin et al [22] found.…”
Section: Resultssupporting
confidence: 90%
“…Gas pressure provides the highest contribution to the influence on the HAZ, and the minimum HAZ responses are recorded at the higher value of assist gas pressure, which can be explained as an increase in the rate of cooling associated with the increase in gas flow rate due to the increase in its pressure. This result was contrary to what Tamrin et al [ 22 ], Renu Tewari et al [ 23 ], Jose Mathew. [ 30 ], and Dalibor Petković [ 32 ] found, as traverse speed had the most considerable effect on the HAZ in their studies.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…It causes undesirable alterations to the local microstructure and properties of the material adjacent to the cut and burning of the edges of holes in laser drilling. 187,188 The results suggest that the type of assist gas used can have an overall effect upon the quality of the holes. The FRP that had been processed with the CO 2 assist gas showed an improved surface quality.…”
Section: Challenges In Machining Of Nfrcsmentioning
confidence: 97%
“…Tewari et al. 187 focused on the investigation of the effects of laser power and cutting speed on hole quality characteristics in laser-drilled kenaf/high-density polyethylene composites. The results show that CO 2 laser is capable of drilling natural composite and optimum laser drilling parameters can yield improved quality of the drilled holes.…”
Section: Processing Of Nfrcsmentioning
confidence: 99%